ATLETSKE DISCIPLINE NA SVEČANIM IGRAMA U OLIMPIJI - Violeta Šiljak (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
Athletics has been developing, and it has been present, more or less, through all the times in all social systems. The majority of studies concerning athletics so far has been pointed out the problems regarding the training process, while just a small number of works has been concerned with the performance techniques. Many of the researchers have come up with incorrect, contradictory, analyses, descriptions or assumptions on possible ways of performing athletic events at the Festivities in Olympia. Thus a challenge was posed to make the experiment of performing the athletic events, especially under the same conditions under which they used to be performed at the Festivities in Olympia (the length of the track, sandy flat ground, requisites - discus, javelin, halteres), in order to find out authentic way of performing the events. During this research the hystorical, experimental and statistical methods were applied.